Polytraumatized. Challenges and perspectives - Ruso, Luis; Voelker, Ricardo (Cirugía del Uruguay, 2001)
In Uruguay casualties represent almost 5% of al/ deaths. Over 70 casualties per mil/ion inhabitants occur and these figures fol/ows an upward trend. Occupational accidents affect 30,000 workers/ year and 500 of them remain with permanent seque/ae.